Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1159/000477804
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of Grooming and Tool Use in a Group of Captive Bonobos (Pan paniscus)

Abstract: Humans exhibit population level handedness for the right hand; however, the evolution of this behavioral phenotype is poorly understood. Here, we compared the laterality of a simple task (grooming) and a complex task (tool use) to investigate whether increasing task difficulty elicited individual hand preference among a group of captive bonobos (Pan paniscus). Subjects were 17 bonobos housed at the Columbus Zoo and Aquarium. Laterality of grooming was recorded using group scans; tool use was recorded using all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the last decades, studies evaluating hand preference in non‐human primates have increased greatly, both in captive and wild populations, and various authors suggested that a right hand bias at the population level does occur in non‐human primates (Hopkins et al, ; Humle & Matsuzawa, ; Llorente et al, ; Lonsdorf & Hopkins, ; Molesti, Vauclair, & Meguerditchian, ; Neufuss, Humle, Cremaschi, & Kivell, ; Poindexter, Reinhardt, Nijman, & Nekaris, in press; Regaiolli, Spiezio, & Hopkins, , 2018; Spinozzi, Castorina, & Truppa, ; Tabiowo & Forrester, ), but this right hand bias is not as strong and stable across different tasks as in humans (Cashmore, Uomini, & Chapelain, ; Marchant & McGrew, ). Other studies, however, with the same and different species report that lateralization in hand preference occurs only at an individual level (Brand et al, ; Leca, Gunst, & Huffman, ; Lilak & Phillips, ; Marchant & McGrew, ; Meunier & Vauclair, ; Papademetriou, Sheu, & Michel, ; Westergaard & Suomi, ).…”
Section: Introductionmentioning
confidence: 94%
“…In the last decades, studies evaluating hand preference in non‐human primates have increased greatly, both in captive and wild populations, and various authors suggested that a right hand bias at the population level does occur in non‐human primates (Hopkins et al, ; Humle & Matsuzawa, ; Llorente et al, ; Lonsdorf & Hopkins, ; Molesti, Vauclair, & Meguerditchian, ; Neufuss, Humle, Cremaschi, & Kivell, ; Poindexter, Reinhardt, Nijman, & Nekaris, in press; Regaiolli, Spiezio, & Hopkins, , 2018; Spinozzi, Castorina, & Truppa, ; Tabiowo & Forrester, ), but this right hand bias is not as strong and stable across different tasks as in humans (Cashmore, Uomini, & Chapelain, ; Marchant & McGrew, ). Other studies, however, with the same and different species report that lateralization in hand preference occurs only at an individual level (Brand et al, ; Leca, Gunst, & Huffman, ; Lilak & Phillips, ; Marchant & McGrew, ; Meunier & Vauclair, ; Papademetriou, Sheu, & Michel, ; Westergaard & Suomi, ).…”
Section: Introductionmentioning
confidence: 94%
“…An HI of -1 represents a totally left-handed individual and an HI of +1 represents a totally right-handed individual. A one-sample binomial test for each slow loris in the unimanual reach and grasp task determined the significant bias in the use of the right or left hand (Brand, Marchant, Boose, White, Rood, & Meinelt, 2017). To analyse the unimanual task and spontaneous unimanual grasping at the group-level, we performed a one-Sample T-test on the distribution of the Absolute Handedness index (ABS-HI) with significance set to p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a large sample size of chimpanzees, Hopkins and colleagues have consistently found that captive chimpanzees show a population-level right-hand bias for unimanual (e.g., reaching for food) and bimanual coordination tasks (e.g., tool use or solving the 'tube task' described below), as well as for communicative, manual gestures (Hopkins, Mareno, and Schapiro 2019;Hopkins, Russell, Freeman, et al 2005;Hopkins, Russell, Hook, et al 2005). However, many studies fail to find population-level biases in ape hand-use, including chimpanzees, even when employing similar methods (Brand et al 2017;Lambert 2012;Motes-Rodrigo, Hernandez-Aguilar, and Laska 2019;Prieur et al 2018) The significance of the corpus of captive research on primate handedness lies in its rich set of cross-species experiments whereby a standardized set of tasks and methods permits robust inferences. For example, a comparison of 777 captive great apes, including gorillas, bonobos, chim-Words, Bones, Genes, Tools: DFG Center for Advanced Studies panzees and orangutans found population-level right-hand bias in all apes for a bimanual coordinated task, excluding the orangutan (Hopkins et al 2011).…”
Section: Population-level Handedness In Captive Nonhuman Pri-matesmentioning
confidence: 99%